Agriculture Development Strategy Shallots (Allium Ascalonicum L) in Kota Padangsidimpuan - Amran Jambak, Ali; Sutan Pulungan; Erwin Syah Lubis; Rasmita Adelina; Juli Yusran (PT Inovasi Pratama Internasional, 2025)
This Research aims to develop a strategy for the development of shallots in Padangsidimpuan. The research used SWOT analysis. It is SWOT matrix which is produce four strategy alternatives. Thsi Swot analysis can describe how is the opportunitis and external threats which is faced by the company. It also describes its strengths and the weaknesses. The result shows that the strategy to increase onion production in the study area is an aggressive strategy and SO strategy (Strengths – Oppurtunities) by using the strength and taking the existence of opportunities with some activities as follows: (1) increasing the stimulus to develop the onion for the farmer and the groupof farmer in Padangsidimpuan. (2) increasing the quality of the farmer by conducting the development of shallots, such as giving training and technical guidance. (3) improving mentoring nad supervision of farmers through formal activities. (4) formulate the system of goverment policies or regulations that are able to create a condusive atmosphere and business climate in the cultivation and trading shallots